2017
DOI: 10.1038/s41598-017-04994-x
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ATG5-dependent macroautophagy by chaperone-mediated autophagy promotes breast cancer cell metastasis

Abstract: Recent data have shown that the expression of lysosome-associated membrane protein type 2 A (LAMP2A), the key protein in the chaperone-mediated autophagy (CMA) pathway, is elevated in breast tumor tissues. However, the exact effects and mechanisms of CMA during breast cancer metastasis remain largely unknown. In this study, we found that the LAMP2A protein level was significantly elevated in human breast cancer tissues, particularly in metastatic carcinoma. The increased LAMP2A level was also positively correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 36 publications
0
64
0
Order By: Relevance
“…Induction of CMA compensates for the impairment of macroautophagy to promote hepatocellular carcinoma cell survival in the cirrhotic liver 34 . CMA-mediated anti-macroautophagic property is a key feature of tumorigenesis and metastasis in breast cancer 35 . Our recent study also showed that SNX10 KO inhibited macroautophagy, while increased CMA activity, promoting tumorigenesis and progression of colorectal cancer in male mice 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Induction of CMA compensates for the impairment of macroautophagy to promote hepatocellular carcinoma cell survival in the cirrhotic liver 34 . CMA-mediated anti-macroautophagic property is a key feature of tumorigenesis and metastasis in breast cancer 35 . Our recent study also showed that SNX10 KO inhibited macroautophagy, while increased CMA activity, promoting tumorigenesis and progression of colorectal cancer in male mice 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AMPK-mediated PLIN2 phosphorylation was required for CMA-mediated PLIN2 degradation, revealing a new role of AMPK in stimulating lipid droplet breakdown during starvation [ 273 ]. The role of CMA in the adaptation of cancer cells to stress is currently unknown, but elevated CMA activity has been recently associated with increased growth and metastasis of breast cancer cells in vitro and in vivo [ 274 ]. Future studies will provide insights into the potential connections between CMA and lipid droplet metabolism in regulating the cancer cell stress response.…”
Section: Lipid Droplets and Autophagy/lipophagymentioning
confidence: 99%
“…Depending on the way a lysosome accepts the substance to be degraded, autophagy can be divided into macroautophagy, microautophagy and chaperone-mediated autophagy. Macroautophagy, the usual form of autophagy, is the most common type and is characterized by the formation of cup-shaped bilayer membrane structures surrounding the cytoplasmic component, followed by the formation of autophagosomes (15)(16)(17)(18). The outer membrane of autophagosomes and the enzymatic fusion form a monolayer membrane structure of autophagosomes, while the inner membrane and contents of autophagosomes are digested (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%